Effect of compost and natural rocks as partial substitutes for NPK mineral fertilizers on yield and fruit quality of ‘Flame’ seedless grapevine grown in two different locations of Egypt - Slama, Mohyeldein I.; Omar, Alaa E. K.; Bassiony, Saber S.; Ghoneem, Ghoneem M. (Spanish Journal of Agricultural Research, 2019)
Aim of study: To evaluate the use of compost and natural rocks as partial replacement of mineral fertilizers in ‘Flame’ seedless grape vineyards.Area of study: The present work was conducted during three successive seasons (2016, 2017 and 2018), being the first season a preliminary trial on 4-yr old grapes cultivated in two different soil types (sandy and clay) at two different locations, Egypt (Abo Galeb, Giza governorate; EL-Mahala, Gharbia governorate).Material and methods: Treatments were applied as natural raw materials at 20, 40, 60, 80 and 100% out of recommended mineral NPK rate. The mineral fertilizers used were ammonium sulfate (21.6% N), calcium super phosphate (15.5% P2O5) and potassium sulfate (48% K2O). The natural rocks used were phosphate rock (22.0% P2O5) and Feldspar (10.12% K2O). Yield and fruit characteristics and leaf mineral content were determined.Main results: Using compost in combination with natural rocks enriched with NPK mobilization bacteria and mineral NPK enhanced leaf nutrients content and gave the highest yield and cluster weight. This mix also improved berries physical and chemical characteristics. There was an increase in soluble solids content (SSC), SSC/acid ratio, and anthocyanin content, associated with a reduction in nitrate content of the berry juice. The most pronounced effect was related to using 60% mineral fertilization + 40% organic and natural rocks in both vineyard locations.Research highlights: We can reduce the recommended doses of mineral NPK by about 40%, reducing then the soil pollution.